Determination of the critical exponent for high temperature superconductors using paraconductivity approach - Md. Ashadul Islam; M. A. Islam (Universitas Sebelas Maret, 2026)
We have developed theoretical ideas to determine the critical exponent, understanding superconductivity for high-temperature superconductors. A detailed analysis is given based on the paraconductivity approach and compared with the experimental results. To develop the theoretical idea, the analysis is performed with the help of well-known paraconductivity expressions. To match the theoretical idea with experimental value, we have reproduced the data points using the ‘OriginPro’ software. Numerical estimation has been given in favour of the samples Tl2Ba2CaCu2O8 (TBCCO), Bi1.6Pb0.4Sr2Ca2Cu3Ox (BSCCO), (YBCO) and (SmBCO). The theoretical models largely agreed with the experimental results for the mentioned superconducting samples.